Refractory ovarian squamous cell carcinoma arising from a seromucinous borderline tumor with squamous overgrowth: A case report - Ryo Tamura; Naohisa Kushiya; Masayuki Yamaguchi; Nobumichi Nishikawa; Teiichi Motoyama; Takashi Kawasaki; Akira Kikuchi (Elsevier, 2024)
Ovarian squamous cell carcinoma (SCC) is rare, and most cases arise from ovarian teratomas. Herein, we present a case of ovarian SCC arising from an ovarian seromucinous borderline tumor (SMBT) with squamous overgrowth. A 71-year-old woman an underwent emergency laparotomy due to the rupture of a right ovarian tumor suspected to be a borderline or malignant tumor. We performed a total abdominal hysterectomy, bilateral salpingo-oophorectomy, and partial omentectomy. The postoperative diagnosis was stage IC3 ovarian SCC arising from the SMBT with a squamous overgrowth. Subsequently, she underwent six cycles of combination therapy comprising paclitaxel and carboplatin. Two months after the last chemotherapy treatment, she presented with back pain. A CT scan showed a 14 mm pelvic tumor affecting the ureter, leading to right hydronephrosis. The patient underwent tumor resection and ureteroureterostomy. The pathological diagnosis was keratinizing SCC, representing ovarian cancer recurrence. Eight months after the removal of the recurrent tumor, we found a 35 mm recurrent pelvic tumor causing right hydronephrosis. Additionally, a 20 mm pleural dissemination was identified. Comprehensive genome profiling of recurrent tumor revealed genomic abnormalities in TP53, ARID1A, PTEN, PIK3R1, and CDKN2A/2B. Regarding immunotherapy biomarkers, the microsatellite instability test result was negative, the tumor mutation burden was low, and PD-L1 was highly expressed. The patient was referred to another hospital for participation in an immunotherapy clinical trial for ovarian SCC. This case indicates that refractory ovarian SCC can arise from SMBT. Further evaluation of additional cases is required to identify the molecular biological characteristics of ovarian SCC.